The Validity and Effectiveness of Customary Law-Based Environmental Management for The Sustainability of Natural Resources - Sri Handayani; Indrahayu Mattalitti Umar Gazali; Wahid Yaurwarin; Raodiah Raodiah; Wahyuni Idrus (Postgraduate, University of Mataram, 2023)
Environmental damage in Indonesia is increasingly apprehensive. Massive forest exploration has threatened the ecosystem. Natural disasters such as overflowing rivers, landslides, and climate change are becoming more frequent. Buntu Batu Traditional Village is located in the Pangkep Regency Area and has customary law that supports forest conservation. Voluntary and sustainable reforestation of communities as a condition for marriage. Preliminary observations indicate that community understanding of the legal aspects of forest conservation is still lacking. They protect the forest for the sake of environmental sustainability. The basis of this action is to follow the customary rules that apply in the Buntu Batu Traditional Village. This study aims to examine the validity and effectiveness of customary law in environmental management in the Buntu Batu Traditional Village, Pangkep. This research is a qualitative study. The village head who also acts as the traditional leader along with 3 local people became participants in this study. Researchers live and mingle with the community to see and observe forest management based on their customary rules. Based on the results of the study, the customary law in force in Buntu Batu Pangkep Village fulfills the validity and effectiveness requirements socially, juridically and morally